Measure Accurately, Act Rapidly, and Partner With Patients (MAP) improves hypertension control in medically underserved patients: Care Coordination Institute and American Medical Association Hypertension Control Project Pilot Study results. Issue 1 (5th January 2018) - Hanlin, Robert B.; Asif, Irfan M.; Wozniak, Gregory; Sutherland, Susan E.; Shah, Bijal; Yang, Jianing; Davis, Robert A.; Bryan, Sean T.; Rakotz, Michael; Egan, Brent M.
Abstract : Measure Accurately, Act Rapidly, and Partner With Patients (MAP) is an evidence‐based protocol implemented to improve hypertension control in a clinic for underserved patients (49.9% Medicaid and 50.2% black). Patients with hypertension seen during the year before intervention and with at least one visit during the 6‐month intervention (N = 714) were included. If initial attended blood pressure (BP; standard aneroid manometer) was ≥140/≥90 mm Hg, unattended automated office BP was measured in triplicate and averaged (Measure Accurately) using an Omron HEM‐907XL. When automated office BP was ≥140/≥90 mm Hg, Act Rapidly included intensification of antihypertensive medications, assessed by therapeutic inertia. Partner With Patients included BP self‐monitoring, reducing pill burden, and minimizing medication costs, which was assessed by systolic BP change per therapeutic intensification. Between baseline and the last study visit, BP control to <140/<90 mm Hg increased from 61.2% to 89.9% ( P  < .0001). MAP rapidly and significantly improved hypertension control in medically underserved patients, largely as a result of measuring BP accurately and partnering with patients.